Making micro-credentials work for learners, employers and providers. - Oliver, Beverley (Deakin University, 2019)
This report explores how micro-credentials might play a central role in re-forming pre and particularly post Bachelor education. Many micro-credentials are already well-respected and robust stand-alone signals of achievement. With careful thought, however, micro-credentials that emulate the standards expected in formal qualifications might bridge the current gap between the existing robust system of qualifications and the fledgling yet rather chaotic world of emerging micro-credentials. Interoperability between the two systems would be to the advantage of learners, employers, providers and policy makers. Whether in a formal qualification or in a micro-credential, the certification is the proof point of skills achieved and knowledge acquired. As the future of work unfolds, working citizens are likely to need more and better granular certified learning micro and macro to evidence their educational currency amid rapid change. Micro-credentials are one way to enable certification of new skills, as well as validate the skills already acquired through experience. [Publisher summary, ed]